(untitled) (Entrepreneurship Journal for Finance and Business, 2023)
The importance of the current research stems from clarifying the effect of soft power as an independent variable in achieving job satisfaction as a dependent variable, as the research seeks to how to benefit from the methods of rational decisions by decision makers in order to consolidate the principles of job satisfaction among workers in a governorate education directorate, The descriptive analytical approach was adopted to complete the research, as a number of main and sub-hypotheses were tested to indicate the relationships of correlation and influence, and answers to the questions of the research problem were reached, as an intentional sample was chosen, represented by (36) decision-makers in the Governorate Education Directorate Anbar, the questionnaire was adopted as a main tool for collecting information, as the information was analyzed and processed according to the statistical program (SPSS), and the means represented by the arithmetic mean, the weighted standard deviation, and the relative importance were used. Anbar in the process of communication and communication between the members of the organization. As for the most prominent recommendations of the research, the organization should encourage the spirit of teamwork among the members of the organization in order to reach the desired goals.